“There was a Man Sent from God …” (J 1, 6). St. John the Baptist in the View of the Author of the Fourth Gospel - Nalewaj, Aleksandra (Studia Warmińskie, 2014)
Every evangelist is familiar with the character of St. John the Baptist. While the Synoptic Gospels tend to show him as the predecessor of the Messiah who paves the way for Him, in the Fourth Gospel he appears as a figure witnessing the Approaching One. Thanks to God's revelation John was able to recognize Christ when He came, and bear witness to Him. Openness to “the might from heaven” and complete availability meant that Baptist read his mission properly, not overshadowing the Son of God with his presence. Although he did not join in the messianic movement and did not follow Jesus, which is an important feature of his followers, in the Fourth Gospel he performs the function of a “prototype of a disciple of Christ”.